Land policy in the development of agriculture: The responses of farmers in Ondo and Oyo States of Nigeria to the Land Use Act - FABIYI, YAKUB L. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The Federal Military government reformed the Nigerian customary Land tenure system by fiat through the proclamation of a Land Use Decree (Act) in 1978, which purports to take over the administration and control of land in the country. This study, designed to identify the responses of farmers to the land reform, was conducted among farmers in Ondo and Oyo states. The study revealed that majority of the respondents do not favour the decree because it conflicts with the accepted norm. The decree has not stopped speculation on land, it has only driven it underground. It has not made it easier for any non-members of land owning families to secure an allocation of land. Not many farmers have applied for certificate of occupancy and the few who applied had difficulties in obtaining the certificate. The study concludes that the decree needs to be appropriately reviewed to make it more acceptable and administratively workable.